Serum Albumin's Protective Inhibition of Amyloid-β Fiber Formation Is Suppressed by Cholesterol, Fatty Acids and Warfarin. Issue 7 (30th March 2018) - Bode, David C.; Stanyon, Helen F.; Hirani, Trisha; Baker, Mark D.; Nield, Jon; Viles, John H.
Abstract: Central to Alzheimer's disease (AD) pathology is the assembly of monomeric amyloid-β peptide (Aβ) into oligomers and fibers. The most abundant protein in the blood plasma and cerebrospinal fluid is human serum albumin. Albumin can bind to Aβ and is capable of inhibiting the fibrillization of Aβ at physiological (μM) concentrations. The ability of albumin to bind Aβ has recently been exploited in a phase II clinical trial, which showed a reduction in cognitive decline in AD patients undergoing albumin–plasma exchange. Here we explore the equilibrium between Aβ monomer, oligomer and fiber in the presence of albumin. Using transmission electron microscopy and thioflavin-T fluorescent dye, we have shown that albumin traps Aβ as oligomers, 9 nm in diameter. We show that albumin-trapped Aβ oligomeric assemblies are not capable of forming ion channels, which suggests a mechanism by which albumin is protective in Aβ-exposed neuronal cells. In vivo albumin binds a variety of endogenous and therapeutic exogenous hydrophobic molecules, including cholesterol, fatty acids and warfarin. We show that these molecules bind to albumin and suppress its ability to inhibit Aβ fiber formation. The interplay between Aβ, albumin and endogenous hydrophobic molecules impacts Aβ assembly; thus, changes in cholesterol and fatty acid levels in vivo may impact Aβ fibrillization, by altering the capacity of albumin to bind Aβ. These observations are particularly intriguing given that high cholesterol or fatty acid diets are well-established risk factors for late-onset AD. Graphical abstract: Highlights: Albumin binds to Aβ, inhibiting fiber formation at physiological (μM) concentrations. TEM indicates that albumin kinetically traps Aβ as oligomers, 9 nm in diameter. Albumin-trapped Aβ oligomeric assemblies are incapable of forming ion channels. Cholesterol, warfarin and fatty acids suppress albumin's amyloid inhibiting properties. Aβ clearance from the brain by albumin may be impacted by cholesterol and fatty acids levels.